Tác động của học hỏi tổ chức tới kết quả hoạt động trong các doanh nghiệp Việt Nam - Nguyễn Duy, Thành (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This paper analyzes the relationship between organizational learning, knowledge process capability, and firm performance across 284 manufacturing enterprises in 25 provinces and cities in Vietnam. Among these variables, organizational learning and firm performance are first-order constructs, while knowledge process capability is a second-order construct, comprising four latent variables, including: knowledge acquisition, knowledge transfer, knowledge application, and knowledge protection. The estimation results based on the partial least squares structural equation modeling (PLS-SEM) indicate that organizational learning and knowledge process capability positively influence firm performance. However, knowledge process capability has a greater effect on firm performance than organizational learning. Furthermore, the knowledge process capability plays a mediating role in the relationship between organizational learning and firm performance in Vietnamese enterprises.
Keywords: Organizational learning; Knowledge process capability; Firm performance